2005
DOI: 10.1238/physica.topical.115a00294
|View full text |Cite
|
Sign up to set email alerts
|

Short Range Structure of Lanthanum ChlorideOxychloride Determined by EXAFS

Abstract: Transmission XAFS measurements were performed on lanthanum chloride (LaCl 3 ) and LaCl 3 -Li 2 O mixture at various temperatures using La-K X-ray absorption edge. A distinct phase shift in the EXAFS oscillations was observed in going from the solid phase to the molten phase in LaCl 3 . The results of curve fitting to the predominant peak in the structure function of LaCl 3 in real space, corresponding to the La 3+ -Cl − 1st coordination shell, reveal that both the interionic distance and coordination number of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 5 publications
2
5
0
Order By: Relevance
“…Overall, these results showed a total CN of 5.7(3). This Cl 1– CN seemed reasonable, especially in the context of previous studies that showed that LnCl 3 transitioned when heated in molten salts to penta-, hexa-, and hepta-coordinate lanthanides. , It was also satisfying to see the agreement between our experimental and theoretical Cl 1– CNs reported herein (vida infra). The EXAFS data confirmed the presence of a shell of K 1+ cations with an occupancy of number of 2(1) and an Eu···K 1+ distance of 4.350(2) Å.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…Overall, these results showed a total CN of 5.7(3). This Cl 1– CN seemed reasonable, especially in the context of previous studies that showed that LnCl 3 transitioned when heated in molten salts to penta-, hexa-, and hepta-coordinate lanthanides. , It was also satisfying to see the agreement between our experimental and theoretical Cl 1– CNs reported herein (vida infra). The EXAFS data confirmed the presence of a shell of K 1+ cations with an occupancy of number of 2(1) and an Eu···K 1+ distance of 4.350(2) Å.…”
Section: Resultssupporting
confidence: 88%
“…We also acknowledge that there were subtle differences fom the solid state europium EXAFS results (reported here) and those from La, Ce, Nd, and Sm in molten chloride and fluoride liquid phase. 41,44,45 Hence, we expect that our experimental measurements and calculation results may have some subtle differences.…”
Section: Coordination Structure Of Eucl N In Molten Saltsmentioning
confidence: 96%
“…In the previous XAFS experiments on LaCl 3 [9], we mixed the salts with BN matrix powder to prepare pellets, which kept the molten salts in a homogeneous dispersed state. Although conscientious efforts were made to follow all the experimental procedures and useful information obtained for future studies, the inter-ionic distance in the liquid phase was rather underestimated in comparison with the value derived from diffraction techniques [3][4][5] and the other XAFS study [10].…”
Section: Resultsmentioning
confidence: 99%
“…To resolve these contradictions, we have performed extended X-ray absorption fine structure (EXAFS) experiments that allow us to investigate the local structure only around the Xray absorption atom. This information is quite useful not only to refine the inter-ionic potentials used in molecular dynamics simulations [8], but also for practical applications, such as the pyrochemical treatment of spent nuclear fuels in the nuclear engineering field [9].…”
Section: Introductionmentioning
confidence: 99%
“…It is negligible in Y-type systems 174 while it is clear in La-type systems. 175 Among these two groups LaCl 3 and YCl 3 have been extensively studied; we will therefore take them as references to depict the structure of molten rare earth halides. We will then show how the structure is modified by changing the cation and/or the halide species.…”
Section: Iii31 Rare Earth Metal Halidesmentioning
confidence: 99%